Engineering properties of alkali activated materials reactive powder concrete. (15th February 2021) - Alharbi, Yousef R.; Abadel, Aref A.; Salah, Abdulrahman A.; Mayhoub, Ola A.; Kohail, Mohamed
Highlights: RPC based AAM promotes the production of sustainable high strength concrete. Alkali Activated Metakaoline RPC achieves satisfying results in mechanical strength. Microwave is the best curing in RPC-AAM due to acceleration in geopolymerization. Water in AAM weakens the geopolymerization so increase porosity of microstructure. Abstract: Reactive Powder Concrete (RPC) is considered a high strength concrete that exhibits a high mechanical and durability properties. Its development requires a high cement demand. Cement production is not a sustainable eco-friendly process. So there is a need to replace the utilization of cement with partially or totally environmental friendly Alkali Activated Materials (AAM) binders. The main aim of this study is to evaluate the performance of RPC developed by AAM under different curing conditions. The utilized AAM in this research are slag and Metakaoine (MK) which are quite available in Middle East. Among the engineering properties studied were the compressive strength, the elastic modulus, porosity and the sorptivity tests. Scanning Electron Microscope (SEM), Energy-Dispersive X-ray (EDS) Spectroscopy and Mercury Intrusion Porosimetry (MIP) tests were also performed to investigate the concrete microstructure for the mixes under different curing conditions. It was concluded that microwave curing has shown a good impact in the performance of AAM mixes with total replacement of cement more than in the AAM mixes with partial replacement of cement. Steam curing enhances the behaviour of the RPC based cement than microwave curing does. Also a loss in strength reached 30% was observedwhen MK was used in RPC based AAM when compared with slag. MIP measurements proved that the microwave curing leads to reduction of capillary pores. Additional water added to improve the workability of RPC based AAM leads to weaken the geopolymerization process and hence increase the porosity of the microstructure.